Knowledge management strategies a handbook of applied technologies - Lytras, Miltiadis D. 1973- (Knowledge and learning society book series, 2008)
"This book provides practical guidelines for the implementation of knowledge management strategies through the discussion of specific technologies and taxonomies of knowledge management applications. A critical mass of some of the most sough-after research of our information technology and business world, this book proves an essential addition to every reference library collection"--Provided by publisher.